Empowering Early Childhood Educators: Using Islamic Heroes to Instill Heroic Values in Early Childhood - Fatwikiningsih, Nur (Southeast Asian Journal of Islamic Education, 2024)
Few studies have investigated educators' roles in instilling heroic values in early childhood through Islamic heroes. Educators play a crucial role in shaping early childhood’s understanding of heroism, primarily through Islamic heroes, because early childhood commonly has misconceptions about heroes. They often struggle to articulate these ideas and frequently associate heroism with fictional characters from storybooks, movies, or fairy tales. The purpose of this research is to explore the role of educators in professional development in learning and teaching early childhood, which is connected with moral lessons about heroic values using Islamic heroes. This study used a qualitative method with interviews and documentation. Participants were seven early childhood educators from seven different schools. The data analysis technique used Braun and Clarke’s thematic analysis. The results show that educators often have misconceptions about the meaning of heroes and heroism, particularly regarding Islamic heroes. The selection of teaching materials indicates limitations in educators' ability to explore Islamic heroes and appreciate the richness of Islamic heroism. The material presented emphasizes aspects of religious practice and sainthood rather than describing and instilling heroic values. The implementation strategy includes lesson plans and teaching materials (selecting Islamic figures, the content of narratives, and Islamic hero's storytelling techniques) focusing more on history, religiosity, and worship aspects of Wali Songo and Prophets of Islam. Educators should create learning activities with storytelling according to the age of children; new concepts should be introduced with brief explanations, a variety of media should be used to visualize stories, and storytelling should keep children focused.